2009
DOI: 10.1021/bi901314c
|View full text |Cite
|
Sign up to set email alerts
|

Cystic Fibrosis Transmembrane Conductance Regulator: Using Differential Reactivity toward Channel-Permeant and Channel-Impermeant Thiol-Reactive Probes To Test a Molecular Model for the Pore

Abstract: The sixth transmembrane segment (TM6) of the CFTR chloride channel has been intensively investigated. The effects of amino acid substitutions and chemical modification of engineered cysteines (cysteine scanning) on channel properties strongly suggest that TM6 is a key component of the anion-conducting pore, but previous cysteine-scanning studies of TM6 have produced conflicting results. Our aim was to resolve these conflicts by combining a screening strategy based on multiple, thiol-directed probes with molecu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

28
180
0

Year Published

2011
2011
2014
2014

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 68 publications
(208 citation statements)
references
References 56 publications
28
180
0
Order By: Relevance
“…Selectivity arises because those anions that partition more effectively into the pore from water (e.g., SCN) also reside longer on average within the pore (bind more tightly) because of a greater difference between their interaction energies with water (hydration energies) and with the lower dielectric pore interior (solvation energies). To a first approximation this bias-type selectivity mechanism (Smith et al 1999) describes how permeant anions traverse the CFTR pore with of course the limit that some anions are too big to pass through the pore in the first place (Alexander et al 2009). …”
Section: Anion Selectivitymentioning
confidence: 99%
See 2 more Smart Citations
“…Selectivity arises because those anions that partition more effectively into the pore from water (e.g., SCN) also reside longer on average within the pore (bind more tightly) because of a greater difference between their interaction energies with water (hydration energies) and with the lower dielectric pore interior (solvation energies). To a first approximation this bias-type selectivity mechanism (Smith et al 1999) describes how permeant anions traverse the CFTR pore with of course the limit that some anions are too big to pass through the pore in the first place (Alexander et al 2009). …”
Section: Anion Selectivitymentioning
confidence: 99%
“…Linsdell et al (2000) first reported that mutations at residues F337 and T338 in TM6 strongly affected the permeability sequence. Those findings were extended by testing additional TM6 mutants Ge et al 2004) and by using cysteine scanning to explore the accessibility of TM6 residues (Alexander et al 2009;Bai et al 2010;El Hiani and Linsdell 2010). Alexander et al (2009) compared the effects of two types of reactive compounds on a series of TM6 cysteine mutants: large methanethiosulfonate (MTS) compounds that are not expected to traverse the pore and smaller pseudohalides that both traverse the CFTR pore and are thiol reactive (Ag(CN) 2 and Au(CN) 2 ).…”
Section: Pore-lining Tmsmentioning
confidence: 99%
See 1 more Smart Citation
“…Dysfunction of CFTR is directly associated with three devastating diseases: cystic fibrosis, polycystic kidney disease, and secretory diarrhea. Based on functional data and homology models, CFTR has been predicted to contain five functional domains: two membranespanning domains (MSDs), each including six transmembrane (TM) helices; two nucleotide binding domains (NBD1 and NBD2); and a unique regulatory (R) domain, which carries multiple protein kinase A (PKA) consensus phosphorylation sites and is unique to CFTR in the ABC superfamily (1)(2)(3)(4)(5)(6). Functional studies from multiple groups have suggested that TM6 plays an essential role and TM12 contributes less to anion conduction and permeation properties in the CFTR channel pore (7)(8)(9)(10)(11).…”
mentioning
confidence: 99%
“…The channel state of CFTR in the homology model is unclear, but it is evident that the four salt bridge amino acids sit close to each other. Alexander et al found that Arg 352 and Asp 993 start out quite a distance away from each other in their molecular dynamics simulations of CFTR conformational change and move toward to each other as the simulation progresses toward the open state (3). In the bacterial Na ϩ channel and Kv7.1 channels, it has been reported that dynamic electrostatic interactions are involved in channel gating (17)(18)(19)(20).…”
mentioning
confidence: 99%